Tectonic and hydrothermal activity at the Yellow Lake fissure in response to the 2004 Dallol dyke intrusion event in Afar - Mège, Daniel; Hauber, Ernst; Dyment, Jérôme; Allemand, Pascal; Moors, Hugo; De Craen, Mieke; Choe, Hanjin (Frontiers in Earth Science, 2023)
The Danakil depression in Ethiopia, at the southern end of the Red Sea, has been the place of volcanic crises in 2004-10, with emplacement of at least 15 dykes. One of them, non-emergent, occurred in dry lake Asale next to Black Mountain and south of Mount Dallol during fall 2004. We report on the opening of a 4.5 km-long fissure in the ground at the same time the Black Mountain dyke was intruding the crust 2 km westward and parallel to it. The fissure, located north and south of Yellow Lake (Gaet'ale) and trending NNW-SSE, is still hydrothermally active. First, we describe the remarkable diversity of morphologic expressions of the fissure, made possible by development in an evaporite sequence. Satellite image monitoring reveals that its formation is coeval with the latest intrusion stage of the Black Mountain dyke. Hydrothermal activity in the fissure area is, however older than ~60 years. It is suggested that hydrothermal activity is primarily a side effect of the igneous processes, probably sill intrusion, that resulted in the uplift of Mount Dallol area, in a ~400 m thick, fluid-saturated evaporite pile. We suggest that, in 2004, emplacement of the Black Mountain dyke caused dilation within the evaporite pile overlying it, where extension was also facilitated by pressured pore fluids. This study documents the delicate intermingling of magmatic, tectonic, hydrothermal, and geomorphologic processes in evaporitic environments at the transition between continental rifting and oceanic spreading.